2018
DOI: 10.1542/peds.2017-2862
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Unnecessary Imaging and Pathology Tests: A Systematic Review

Abstract: Promising interventions include audit and feedback, system-based changes, and education. Future researchers should move beyond before-after designs to rigorously evaluate interventions. A relatively novel approach will be to include both clinicians and the families they manage in such interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 68 publications
(38 reference statements)
1
25
0
Order By: Relevance
“…However, this study included both outpatients and all hospitalized patients with acute and chronic pain, so its generalizability to the ED setting is limited. In contrast, a review in the pediatric population found that patient/family education was the single most effective intervention with a relative reduction of 57.9%, and that multi-faceted interventions were more effective than single focused ones [15].…”
Section: Description Of the Existing Intervention Datamentioning
confidence: 87%
See 1 more Smart Citation
“…However, this study included both outpatients and all hospitalized patients with acute and chronic pain, so its generalizability to the ED setting is limited. In contrast, a review in the pediatric population found that patient/family education was the single most effective intervention with a relative reduction of 57.9%, and that multi-faceted interventions were more effective than single focused ones [15].…”
Section: Description Of the Existing Intervention Datamentioning
confidence: 87%
“…Assessing these strategies and their effectiveness at reducing imaging is a popular topic in the literature with several systematic reviews having been published. However, this literature frequently focuses on specific pathologies (e.g., CT use in acute low-back pain patients), includes multiple imaging modalities, or reviews the incidence of low-value testing in general without addressing potential solutions [7,[10][11][12][13][14][15].…”
Section: Description Of the Existing Intervention Datamentioning
confidence: 99%
“…One study found that such a strategy led to a reduction in patients referred to secondary care (5% of patients for the multifaceted strategy group vs 10% of patients in the passive implementation strategy group), and cost reduction (approximately 93£ per patient), however patients were less satisfied [17]. A systematic review regarding the reduction of unnecessary imaging and pathology tests found that the three most effective implementations were multifaceted strategies consisting of three components (45% relative reduction), two components (32% relative reduction), and one component (28.6% relative reduction) [22]. Lastly a multifaceted implementation targeted towards prescribing physicians in a Dutch hospital led to a significant reduction in non adherence (30.5% vs 21.8%) [18].…”
Section: Introductionmentioning
confidence: 99%
“…Other implementation strategies that have had an effect on the use of patient treatment or use of diagnostic testing (including imaging) have been targeted implementation including introduction of the guideline and monthly feedback showing an increase in the adherence rate (baseline 28.1%, vs 61.5% for the targeted strategy) [19]. Interventions targeted towards both the clinicians and the families in their care proved more effective than clinicians only (61.9% [34.3%] vs 30%[32%]) [22], modified referral forms reduced imaging by 36.8% [23] and targeted reminders to primary care physicians of appropriate indications for imaging reduces referrals by 22.5% [23].…”
Section: Introductionmentioning
confidence: 99%
“…Best approaches to improve doctors' use of diagnostic tests have not yet been established, and are likely to involve a number of complementary approaches to convey educational messages to influence decisions about whether or not to order tests. A systematic review of interventions to reduce unnecessary paediatric imaging and pathology testing found that interventions were more effective if they targeted either imaging or pathology testing rather than both simultaneously [13]. Behavioural science provides awareness of the cognitive processes that underpin decision-making and can guide the development of interventions with a view to influencing clinician decision-making in a busy hospital environment.…”
Section: Introductionmentioning
confidence: 99%